Pengaruh Komposisi Bahan Baku Ampas-Kulit Kopi dan Jenis Perekat terhadap Karakteristik Biobriket serta Emisi Gas Rumah Kaca pada Proses Produksi - Delia Anisa Putri; Aussie Amalia (Jurnal Serambi Engineering, 2026)
The utilization of coffee waste as an alternative fuel is a potential strategy in supporting organic waste management and the transition towards renewable energy. This research aims to analyze the effect of variations in the composition of coffee grounds and husk, as well as the type of binder, on the characteristics of bio-briquettes, while also evaluating the greenhouse gas (GHG) emissions generated during their production process using a Life Cycle Assessment (LCA) approach. The experimental method was carried out through the carbonization process of coffee waste at a temperature of 450°C for 80 minutes, followed by mixing the 60-mesh charcoal with bentonite and pulp binders. Characteristic testing, including moisture content, ash content, calorific value, and combustion rate, referred to SNI 01-6235-2000, while the LCA analysis was conducted using SimaPro software with the IPCC GWP100 (2021) method. The results showed that the combination of 100% coffee grounds with a pulp binder produced the best performance with the lowest moisture (4.2%) and ash (1.2%) content, a high calorific value (>6,000 cal/g), and a stable combustion rate. Thus, this combination is recommended as it yields optimal quality while lowering the environmental impact of production. The carbonization stage was the largest contributor to GHG emissions (25.11 kg CO₂-eq/kg product), followed by oven drying (3.77 kg CO₂-eq/kg). These findings affirm the importance of raw material optimization and energy efficiency in enhancing the quality and sustainability of bio-briquette production.